FAKTOR PENGARUH INFLASI TERHADAP PEMBIAYAAN PERBANKAN SYARIAH DI INDONESIA - ARINI PUTRI SAFINA; Sri Wigati (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2022)
Inflation is an increase in the price of basic needs that occurs continuously. Inflation triggers the government to make policies by raising interest rates to attract and reduce the amount of money circulating in the community. This interest rate only applies to conventional banks and does not apply to Islamic banks. So many customers may turn from Islamic banks to conventional banks due to higher savings interest rates. This is finally able to affect the fundraising carried out by Islamic banks and have an impact on the financing of Islamic banks. The research method uses a qualitative literature study. For that type of data using secondary data sourced from the library. Data analysis through data collection, data reduction, presentation, and conclusion. The results of the study state that inflation cannot be a factor that affects Islamic bank financing, this is because of the level of religiosity of customers who do not care about the increase in the interest rate of conventional bank savings and persist with Islamic banks because they want to avoid the sin of usury and the factor of an increase in interest rates. conventional bank loan interest eventually causes many customers to look for financing from Islamic banks. The impact of this research is to strengthen existing research that the inflation factor does not have a close relationship with Islamic banks, so it is natural that in 1998 Islamic banks still existed amid the economic crisis that occurred.